Mapping the implementation of the emerging education model - Spinassé, Marcos Antônio; Debald, Blasius Silvano (Brazilian Journal of Production Engineering, 2021)
In view of the need to adopt adequate procedures for the implementation of a new educational model, we sought to draw up a descriptive mapping of the insertion process that has already been taking place in higher education institutions. The emerging educational model insertion process is configured through a scheme of the higher education institution as an organism composed of three dimensions: (1) Learning System; (2) Administration and (3) Infrastructure. Where, each of the three dimensions (1, 2 and 3) would be seen through three prisms: (A)Agents; (B) Material resources and (C) Processes and their elements.